2017
DOI: 10.1027/1618-3169/a000377
|View full text |Cite
|
Sign up to set email alerts
|

Walking Back to the Future

Abstract: Embodied cognition frameworks suggest a direct link between sensorimotor experience and cognitive representations of concepts ( Shapiro, 2011 ). We examined whether this holds also true for concepts that cannot be directly perceived with the sensorimotor system (i.e., temporal concepts). To test this, participants learned object-space (Exp. 1) or object-time (Exp. 2) associations. Afterwards, participants were asked to assign the objects to their location in space/time meanwhile they walked backward, forward, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Sentences containing temporal information (Eikmeier, Alex-Ruf, et al, 2015, experiment 1;Eikmeier et al, 2013, experiment 1;Scheifele et al, 2018;Sell & Kaschak, 2011;Ulrich & Maienborn, 2010;Ulrich et al, 2012); and 3. Triplets of pictures showing the progression of an event at which the middle stage represents the reference point for an earlier and a later stage Fuhrman & Boroditsky, 2007; and entities such as buildings, actors, or life events that can be categorized as earlier or later compared to some given reference point (Loeffler, Raab, & Cañal-Bruland, 2017;Miles, Tan, Noble, Lumsden, & Macrae, 2011;Walker, Bergen, & N uñez, 2014Weger & Pratt, 2008, experiment 1).…”
Section: Temporal Informationmentioning
confidence: 99%
“…Sentences containing temporal information (Eikmeier, Alex-Ruf, et al, 2015, experiment 1;Eikmeier et al, 2013, experiment 1;Scheifele et al, 2018;Sell & Kaschak, 2011;Ulrich & Maienborn, 2010;Ulrich et al, 2012); and 3. Triplets of pictures showing the progression of an event at which the middle stage represents the reference point for an earlier and a later stage Fuhrman & Boroditsky, 2007; and entities such as buildings, actors, or life events that can be categorized as earlier or later compared to some given reference point (Loeffler, Raab, & Cañal-Bruland, 2017;Miles, Tan, Noble, Lumsden, & Macrae, 2011;Walker, Bergen, & N uñez, 2014Weger & Pratt, 2008, experiment 1).…”
Section: Temporal Informationmentioning
confidence: 99%
“…Of course, there are many ways to continue to look for a link between self-locomotion and memory. For example, other memory paradigms can be used (e.g., see Loeffler et al, 2017 for a procedure which used walking-backward to facilitate the processing of past-related stimuli). Perhaps the to-be-remembered materials should be related to the visual environment; perhaps a manipulation of coherence of movement and optic flow during encoding would be more effective; perhaps effects of movement on memory are prominent during early or late development.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, smaller differences in walking speed ( Experiment 1 ) were expected to lead to a less pronounced effect of walking speed on perceived time, as opposed to larger effects due to larger differences among levels of the same variable ( Experiments 2 and 3 ). Moreover, we expected larger effects when participants timed forward walking as opposed to backward walking motion, in addition to observing higher precision with which durations are timed in the forward walking condition due to it being a more familiar form of motion (i.e., processed more readily) in comparison to backward walking (Moscatelli et al, 2011; Loeffler et al, 2017). While previous research has conclusively demonstrated an effect of low-level motion on time perception (e.g., Kaneko and Murakami, 2009), no study so far has utilized straight-forward representations of human motion through the use of stick-figure actions to test for presumably more readily embodied effect of motion on perceived durations.…”
Section: Introductionmentioning
confidence: 93%